Multicentre, prospective, randomised controlled trial to evaluate hexaminolevulinate photodynamic therapy (Cevira) as a novel treatment in patients with high-grade squamous intraepithelial lesion: APRICITY phase 3 study protocol - Fei Chen; Jinghe Lang; Peter Hillemanns; Youzhong Zhang; Zoltán Novák; Long Sui; Ling Han; Christian Dannecker; Ctirad Mokráš; Zhixue You (BMJ Open)
Introduction High-risk human papilloma virus (HPV)-associated cervical cancer is the fourth most common cancer in women worldwide. Current treatments of high-grade squamous intraepithelial lesion (HSIL) of the cervix are based on invasive surgical interventions, compromising cervical competence and functionality. APRICITY is a multicentre, prospective, double-blind, randomised controlled phase 3 study further evaluating the efficacy and safety of Cevira, an integrated drug-delivery and light-delivery device for hexaminolevulinate photodynamic therapy, which shows promise as a novel, non-invasive outpatient therapy for women with HSIL.Methods and analysis Patients with biopsy-confirmed HSIL histology are invited to participate in the study planned to be conducted at 47 sites in China and 25 sites in Ukraine, Russia and the European Union. The aim is to include at least 384 patients, which will be randomised to either Cevira or placebo group (2:1). All patients will be assessed 3 months after first treatment and a second treatment will be administered in patients who are HPV positive or have at least low-grade squamous intraepithelial lesion. Primary endpoint is the proportion of the responders 6 months after first treatment. Secondary efficacy and safety endpoints will be assessed at 6 months, and data for secondary performance endpoints of the Cevira device will be collected at 3 months and 6 months, in case second treatment was administered. All patients in the Cevira group will be enrolled in an open, long-term extension study for 6 months to collect additional efficacy and safety data (study extension endpoints).Ethics and dissemination The study was approved by the ethics committee of the Peking Union Medical College Hospital and Hannover Medical University, Germany. Findings will be disseminated through peer review publications and conference presentations.Trial registration number NCT04484415; clinicaltrials.gov.